Sustainable Marine Fisheries Management as an Effort to Maintain Fish Resource Resilience - Ahmad Firdaus; Siti Rahmawati; Muhammad Rizky Pratama (Journal of Marine Fisheries, 2025)
Sustainable marine fisheries management has become a critical global issue due to the increasing pressure on fish resources caused by overfishing, environmental degradation, and climate change. Indonesia, as one of the world’s largest maritime nations, faces significant challenges in maintaining fish stock resilience while ensuring food security and livelihoods for coastal communities. This study aims to analyze sustainable marine fisheries management practices as an effort to maintain fish resource resilience by integrating ecological, economic, and social dimensions. The research employed a descriptive-analytical approach based on secondary data obtained from national fisheries statistics, scientific journals, and international reports published between 2015 and 2025. Data were analyzed using a qualitative synthesis method supported by sustainability indicators, including stock status, fishing effort, governance effectiveness, and community participation. The results indicate that sustainable fisheries management, particularly ecosystem-based fisheries management, rights-based fisheries, and the implementation of blue economy principles, significantly contributes to maintaining fish stock resilience. However, governance gaps, weak enforcement, and limited stakeholder integration remain major constraints. This study concludes that strengthening institutional capacity, improving data quality, and enhancing community-based management are essential to achieving long-term sustainability of marine fisheries resources. The findings provide practical and theoretical contributions to fisheries management policy development in Indonesia and other developing maritime countries.